2019
DOI: 10.3389/fneur.2019.01260
|View full text |Cite
|
Sign up to set email alerts
|

Rasch Analysis of the Disability Acceptance Scale for Individuals With Cerebral Palsy

Abstract: Background: Acceptance of disability has been considered an important factor in rehabilitation procedures. The Disability Acceptance Scale (DAS) was used in a panel survey, and it is likely that this scale will be increasingly used. This study aimed to determine the psychometric characteristics of the DAS by applying a Rasch model, an application of item response theory.Methods: Data were collected using the DAS with 84 individuals with cerebral palsy. The response data were analyzed for item fitness and item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, scales verified by factor analysis are sometimes adapted and used in other cultures, and sometimes used for groups with different personalities from the target group to which they responded during the scale development. Therefore, to evaluate the fit and difficulty of the items accurately even for the items whose validity has been confirmed through confirmatory factor analysis, it is necessary to verify them with other statistical methods that are less affected by the respondent’s characteristics [ 39 ]. This study identified additional accurate psychometric properties of CDS such as the fit and difficulty of items as compared to Park’s [ 20 ] previous confirmatory factor analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…However, scales verified by factor analysis are sometimes adapted and used in other cultures, and sometimes used for groups with different personalities from the target group to which they responded during the scale development. Therefore, to evaluate the fit and difficulty of the items accurately even for the items whose validity has been confirmed through confirmatory factor analysis, it is necessary to verify them with other statistical methods that are less affected by the respondent’s characteristics [ 39 ]. This study identified additional accurate psychometric properties of CDS such as the fit and difficulty of items as compared to Park’s [ 20 ] previous confirmatory factor analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings of previous studies that report that the phenomenon of depression appeared in the age range of 21 years to 59 years due to factors of productive age (profession and self-confidence) and the feeling of being a burden on others. [ 51 - 53 ]…”
Section: Discussionmentioning
confidence: 99%
“…Other variables appear to play a significant role in psychological adjustment of individuals with SMA. It has been observed that disease acceptance is a correlate or predictor of subjective well-being among individuals with chronic physical disabilities [39,40]. A study among adults with various physical disabilities underscored that acceptance of the illness was positively associated with self-acceptance, well-being, positive relations, family satisfaction, and the presence of meaning, defined as the extent to which individuals grasp, make sense of, and find significance in their lives [41,42].…”
Section: Psychological Adjustment Of Individuals With Smamentioning
confidence: 99%